The Roots and Leaves Character of Drought Tomato on Application of ZnSO4 - Amalia T Sakya; Endang Sulistyaningsih; Didik Indradewa; Benito Heri Purwanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
Application of Zn, beside as an essential nutrient for plants, is known to increase the resistance of plants during drought condition. The purpose of the research was to study the effect of ZnSO4 application on root and leaf character of tomato plants in drought conditions. Research was arranged in factorial randomized completely block design. The treatment consists of ZnSO4 application methods (soil and foliar), ZnS04 dosage (0, 40 and 60 mg Zn kg-1 and cultivars ('Permata’ F1 and 'Tyrana’ F1). Watering intervals of every two and eight days were applied, representing non-stress and drought stress conditions during the growth period of the plant. The results showed that the all response of character roots and leaves of the tomato did not show interaction among the three factors. Root biomass, root length and root surface area of tomato plants depend on the method of application and ZnSO4 dosage. Soil application increased root biomass and root surface area. Root biomass of ‘Permata’ and ‘Tyrana’ showed differences in responses to dosage of ZnSO4. Leaf area responses in both cultivars ‘Permata’ and ‘Tyrana’ showed the same pattern of the ZnSO4 dosage. Response of leaf area ratio at each stage of tomato growth on ZnSO4 application was different.